Antibacterial Activity Test of Turmeric Extract (Curcuma longa) From Madura Island Against Staphylococcus aureus - Baitul Fatimah; Dewangga Sakti Satria Kinasih; Wiwin Retnowati; Yuani Setiawati (Jurnal Kesehatan Prima, 2022)
Staphylococcus aureus is a gram-positive bacteria, a normal flora of the body that can cause infection in various organs and has the potential to become resistant to antibiotics. Turmeric (Curcuma longa) is one of the herbs that has antibacterial effects and is often used by Madurese people as a traditional medicine. It is suspected that geographical differences and the natural conditions in which turmeric grows can affect its compounds and properties. This study aims to analyze the ethanolic extract of turmeric from Madura as an antibacterial against S. aureus. An in vitro laboratory research using agar well diffusion method was conducted with the concentration of turmeric extract used 20%, 40%, 80%, and 100%. The positive control used was penicillin. The negative control in this study was 100% DMSO. The results showed inhibition zone at concentrations of 20% (11.86 mm), 40% (12.04 mm), 80% (12.53 mm), and 100% (10.97 mm). The diameter obtained was lower than the positive control penicillin which was 27.59 mm. Turmeric extract (Curcuma longa) from Madura has antibacterial activity against Staphylococcus aureus.